Host and symbiont genetic contributions to fitness in a Trichogramma–Wolbachia symbiosis - Russell, James E.; Nunney, Leonard; Saum, Michael; Stouthamer, Richard (PeerJ, 2018)
The fitness effects associated with Wolbachia infection have wide-ranging ecological and evolutionary consequences for host species. How these effects are modulated by the relative influence of host and Wolbachia genomes has been described as a balancing act of genomic cooperation and conflict. For vertically transmitted symbionts, like cytoplasmic Wolbachia, concordant host–symbiont fitness interests would seem to select for genomic cooperation. However, Wolbachia’s ability to manipulate host reproductive systems and distort offspring sex ratios presents an evolutionary conflict of interest with infected hosts. In the parthenogenesis-inducing (PI) form of Wolbachia found in many haplodiploid insects, Wolbachia fitness is realized through females and is enhanced by their feminization of male embryos and subsequent parthenogenetic reproduction. In contrast, as long as Wolbachia is not fixed in a population and sexual reproduction persists, fitness for the host species is realized through both male and female offspring production. How these cooperating and competing interests interact and the relative influence of host and Wolbachia genomes were investigated in the egg parasitoid Trichogramma kaykai, where Wolbachia infection has remained at a low frequency in the field. A factorial design in which laboratory cultures of Wolbachia-infected T. kaykai were cured and re-infected with alternative Wolbachia strains was used to determine the relative influence of host and Wolbachia genomes on host fitness values. Our results suggest fitness variation is largely a function of host genetic background, except in the case of offspring sex ratio where a significant interaction between host and Wolbachia genomes was found. We also find a significant effect associated with the horizontal transfer of Wolbachia strains, which we discuss in terms of the potential for coadaptation in PI-Wolbachia symbioses.
Keywords: Wolbachia; Sex ratio; Trichogramma; Parthenogenesis; Fitness